Antibiotic resistance in Escherichia coli from livestock-related sources: A cross-sectional study of feces, soil, and water in a non-urban region - Silalahi, Gustaf Eifel; Widiasih, Dyah Ayu; Susetya, Heru; Nugroho, Widagdo Sri; Drastini, Yatri; Putri, Khrisdiana; Gallantiswara, Putu Cri Devischa; Yudhanto, Setyo; Primatika, Roza Azizah (The International Journal of Tropical Veterinary and Biomedical Research, 2025)
Background and Aim: Antibiotics are one of the most used treatments by farmers, both in commercial and non-commercial livestock operations. The use of antibiotics in animals directly impacts the environment, which can become a significant factor in the spread of antibiotic resistance. The environment plays an essential role for both animals and humans, and contamination caused by uncontrolled environmental factors can lead to health impacts on surrounding populations. One of the contaminants that can threaten the health of animals and humans is the presence of Escherichia coli. The aim of this study was to determine the antibiotic resistance profile of E. coli in environmental samples collected from a non-urban livestock region in Playen, Gunung Kidul Regency, Yogyakarta.Materials and Methods: The data in this study consisted of fifty samples, including fishpond water, wastewater, drinking water, water source, water tank, feces, and soil. The methodology involved bacterial isolation using biochemical tests and antimicrobial resistance testing conducted through the KirbyBauer disk diffusion method.Results: The antibiotics used in this study were streptomycin, penicillin, enrofloxacin, oxytetracycline, and sulfamethoxazole. The results showed that 5% of the samples were resistant to streptomycin, 92% were resistant to penicillin, 0% were resistant to enrofloxacin, 12.8% were resistant to oxytetracycline, and 2.5% were resistant to sulfamethoxazole.Conclusion: The findings indicate a high prevalence of Penicillin-resistant E. coli in environmental samples from non-urban livestock areas, highlighting the potential risk of environmental antibiotic resistance transmission.